Cassava Farming Based On Rural Agribusiness Development - Sari, Yuria; Banowati, Eva; Mustofa, Mohammad Solehatul; Rahmawati, Shintya Novita (Universitas Negeri Semarang, 2020)
Agriculture products need market value increases trough the development of rural agribusiness. The success of the program needs to be supported by the community to create the expansion of marketing access, the sustainability of the agribusiness and strengthening of capital so as to create savings. Community as a regional unit (natural and social), where its members (farmers and non farmers) carry out various daily activities, which are social capital to play an important role in a development process. This research had the following objectivies: a) determining the synergy of participation of each element (farmer and non farmer) in the development of rural agribusiness, b) finding solutions to the participation constraints of each agribusiness chain, and c) finding sub models of community facilities. The research was conducted in Central Java Province as a cassava-producing region and tapioca center, namely in the districts of Pati and. Meanwhile, the objects of the research included : facilitation actions for community empowerment on the job training, agriculture product processing and independent of the rural agribusiness development, community potential, and the establishment of agrbusiness microfinance institutions. There were two populations of this study, they were: area of cassava land and center of agribusiness, and community members consisting of farmers element (cassava farmers), non farmer (owner of agribusiness and workfoces of agribusiness), and off farmers (owner of transport, transport drivers). Sampling technique used in this study was cluster sampling technique to find out agribusiness data and accuracy test of the accuracy of image interpretation in determining the number of samples using the guidelines of BIG (Geographyc Information Institution in Indonesia), as well as simple random sampling technique for agribusiness center. Data analysis technique used was multiple linear regression for participatory synergistic analysis and synthesizing information to be used in formulating alternatives and policy preferenees are expressed comparatively, predicted in quantitative and qualitative languages as the basis for decision making for proverty reduction analysis. Based on the research data, the results of simple linear regression analysis result in a regression equation Y = 5.26 + 18.26X, this shows a positive influence of each variable where X represents the amount of daily cassava production and Y variable represents the number daily income, meaning that there will be an increase in participation synergy if each of these variables is increased in quantity or quantity. Meanwhile, in testing hypotheses between the two variables produces t count of 0.871, where the t table is 0.374 which means t count> t table so that the conclusions obtained are the influence between variables on the magnitude of the synergy of participation from PUAP. According to the calculation of correlation analysis, the results of the calculation of simple linear regression analysis produce a correlation coefficient of 0.801 and a determination coefficient of 0.642, which means that when linked to the interpretation table the correlation coefficient for correlation between variables is in the